2004
DOI: 10.1002/chin.200411274
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Neurotrophin—Receptor Interactions

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 1 publication
0
46
0
Order By: Relevance
“…This region is located in the fifth subdomain of the extracellular domain of TrkB and has been described as the "specificity patch" of the receptor, as it interacts with the N-terminal region of BDNF (26,28). In fact, the N-terminal end of neurotrophins has been shown (a) to be highly variable in terms of amino acid composition, (b) to affect Trk receptor binding and activation capacities, and (c) to fit into a binding pocket formed by a patch of charged amino acids in the fifth subdomain of Trk receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This region is located in the fifth subdomain of the extracellular domain of TrkB and has been described as the "specificity patch" of the receptor, as it interacts with the N-terminal region of BDNF (26,28). In fact, the N-terminal end of neurotrophins has been shown (a) to be highly variable in terms of amino acid composition, (b) to affect Trk receptor binding and activation capacities, and (c) to fit into a binding pocket formed by a patch of charged amino acids in the fifth subdomain of Trk receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling of ANA-12 docking in the specificity patch showed that the molecule nicely fits into the TrkB-d5 ADEB β-sheet and behaves like the N terminus region of BDNF in the binding pocket (26,28). Similarly to NT-4/5 and BDNF, ANA-12 lies against the disulfide bridge formed by Cys302 and Cys347 and interacts with Asp298, His299, and His300.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that TrkB belongs to a large group of tyrosine-kinase receptors, and BDNF as well as NT-4 are the only ligands for this receptor. 21 The human TrkB is a transmembrane glycoprotein type I that consists of 792 AA residues. Its extracellular domain comprises of three tandem leucine-rich motifs, bordered by two cysteine clusters, and trailed by two immunoglobulin (Ig)-like domains, Ig 1 and Ig 2 , 35 where Ig 2 , the closest to cell membrane, is the binding site for BDNF.…”
Section: Bdnf Receptorsmentioning
confidence: 99%
“…20 The three-dimensional molecular structure of BDNF appears to be a homodimer with noncovalent bonds, where each monomer consists of three pairs of anti-parallel β-sheets connected to four loops of β-strands containing 3 disulfide bonds with cysteine knot motif. 21 Besides, the crystallographic BDNF structure is shown in protein databases as heterodimers with NT-3 (code 1B8M) and NT-4 (code 1BND). 22,23 The BDNF human gene is mapped on chromosome 11 between 11p13 and 11p14.…”
Section: Introductionmentioning
confidence: 99%